2016
DOI: 10.1074/jbc.m116.733626
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Precursor Protein (APP) May Act as a Substrate and a Recognition Unit for CRL4CRBN and Stub1 E3 Ligases Facilitating Ubiquitination of Proteins Involved in Presynaptic Functions and Neurodegeneration

Abstract: The amyloid precursor protein (APP), whose mutations cause Alzheimer disease, plays an important in vivo role and facilitates transmitter release. Because the APP cytosolic region (ACR) is essential for these functions, we have characterized its brain interactome. We found that the ACR interacts with proteins that regulate the ubiquitin-proteasome system, predominantly with the E3 ubiquitin-protein ligases Stub1, which binds the NH 2 terminus of the ACR, and CRL4 CRBN , which is formed by Cul4a/b, Ddb1, and Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 143 publications
1
36
0
Order By: Relevance
“…HRD1 interacts with APP through its Proline-rich region, and this interaction reduces Aβ generation through promoting APP ubiquitination and degradation (Kaneko et al, 2010). In addition, APP can bind to ubiquitin E3 ligases Stub1 and CRL4 CRBN through the APP cytosolic region (ACR; Del Prete et al, 2016). ACR promotes the ubiquitination of several presynaptic proteins and regulates neurotransmitter release (Del Prete et al, 2016).…”
Section: Dysregulation Of Ubiquitination In Neurodegenerative Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…HRD1 interacts with APP through its Proline-rich region, and this interaction reduces Aβ generation through promoting APP ubiquitination and degradation (Kaneko et al, 2010). In addition, APP can bind to ubiquitin E3 ligases Stub1 and CRL4 CRBN through the APP cytosolic region (ACR; Del Prete et al, 2016). ACR promotes the ubiquitination of several presynaptic proteins and regulates neurotransmitter release (Del Prete et al, 2016).…”
Section: Dysregulation Of Ubiquitination In Neurodegenerative Diseasesmentioning
confidence: 99%
“…In addition, APP can bind to ubiquitin E3 ligases Stub1 and CRL4 CRBN through the APP cytosolic region (ACR; Del Prete et al, 2016). ACR promotes the ubiquitination of several presynaptic proteins and regulates neurotransmitter release (Del Prete et al, 2016). …”
Section: Dysregulation Of Ubiquitination In Neurodegenerative Diseasesmentioning
confidence: 99%
“…CUL4B is a known E3 ligase that directly regulates protein levels through ubiquitination (30,42). To delineate how CUL4B regulates expression of Cav1.2 and AC6, we examined Cav1.2 and AC6 ubiquitination in CUL4B-overexpressing and control TGP52 cells ( Figure 6A).…”
Section: Cul4b Ablation In Pancreatic δ Cells Other Than β Cells Causmentioning
confidence: 99%
“…Ubiquitin is a 76-amino acid peptide that is covalently attached to lysine residues of a protein cargo via sequential enzymatic reactions of E1, E2 and E3 ubiquitin ligases (35). The E3 ubiquitin ligase(s) specific for APP remains uncertain, but some studies suggest promising candidates (36,37), and a recent GWAS of Caribbean Hispanics identified F-box/leucine rich-repeat protein 7 (FBXL7), a subunit of an E3 ligase, to be associated with LOAD (38). Several reports identify ubiquitination sites on APP (37, 39, 40) or report alterations in A␤ levels due to changes in APP ubiquiti-nation (7,36,41), but they do not investigate in depth of the mechanism underlying this phenomenon or the downstream effects of reduced ubiquitination.…”
mentioning
confidence: 99%